Analisis peran satuan pengawasan internal dan komite audit terhadap pencegahan kecurangan - Komala, Lenda; Asaari, Masagus (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to examine the role of the Internal Audit Unit (SPI), and the Audit Committee, which assist the supervisory function by management and the board of commissioners in preventing fraud that has a negative impact on company performance and state finances. This research is a type of quantitative descriptive research, with the research population being state-owned companies in Indonesia. Primary data was obtained by using a questionnaire technique. To measure the effectiveness of the SPI and the Audit Committee in preventing fraud, the Path Analysis model is used. The results of this study indicate that the effectiveness of the Internal Audit Unit and the Audit Committee has a positive influence on fraud prevention, through improving the company's internal control. Other factors such as corporate culture, leadership as well as sharpening tasks and missions are also quite dominant in preventing fraud.